The Relationship of Big 5 Personality Traits on Investment Decision - Dwi Novira Rahmah (Syntax Corporation, 2023)
The Big Five personality traits, comprising openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism, represent a widely acknowledged framework in the realm of psychological research. These characteristics have shown to be especially important in studies on financial decision-making, especially when it comes to individual investing behavior. Within the framework of this research, which utilizes data from the Indonesian Family Life Survey (IFLS 5), a thorough examination is carried out to reveal the intricate influence of the Big Five personality traits on the investment behavior of households. This study uses probit regression techniques with STATA. The results of the probit regression show that openness to experience has a positive and significant effect while neuroticism has a negative and significant effect on household investment decisions.